2022
DOI: 10.1017/s1431927622000344
|View full text |Cite
|
Sign up to set email alerts
|

Using Xe Plasma FIB for High-Quality TEM Sample Preparation

Abstract: A direct comparison between electron transparent transmission electron microscope (TEM) samples prepared with gallium (Ga) and xenon (Xe) focused ion beams (FIBs) is performed to determine if equivalent quality samples can be prepared with both ion species. We prepared samples using Ga FIB and Xe plasma focused ion beam (PFIB) while altering a variety of different deposition and milling parameters. The samples’ final thicknesses were evaluated using STEM-EELS t/λ data. Using the Ga FIB sample as a standard, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…But the micropillars from magnesium are larger in diameter and we see significantly less implantation of Xe ions on their top surface. On the sidewalls of micropillars the Xe ions should impact with glancing angles (80-90 • ) and implantation depths are lower [13,28,29] and radial. Implantation of Xe in the sidewalls should lead to amorphization as seen in lamellas prepared for TEM studies [10,13,28,29].…”
Section: Angle-dependent Implantation Of Xe + Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…But the micropillars from magnesium are larger in diameter and we see significantly less implantation of Xe ions on their top surface. On the sidewalls of micropillars the Xe ions should impact with glancing angles (80-90 • ) and implantation depths are lower [13,28,29] and radial. Implantation of Xe in the sidewalls should lead to amorphization as seen in lamellas prepared for TEM studies [10,13,28,29].…”
Section: Angle-dependent Implantation Of Xe + Ionsmentioning
confidence: 99%
“…On the sidewalls of micropillars the Xe ions should impact with glancing angles (80-90 • ) and implantation depths are lower [13,28,29] and radial. Implantation of Xe in the sidewalls should lead to amorphization as seen in lamellas prepared for TEM studies [10,13,28,29]. It has been shown that the thickness of amorphization for samples prepared with Xe ions is ~40% less compared to those prepared using a Ga-beam [10].…”
Section: Angle-dependent Implantation Of Xe + Ionsmentioning
confidence: 99%